2017
DOI: 10.1093/brain/awx057
|View full text |Cite
|
Sign up to set email alerts
|

Biochemically-defined pools of amyloid-β in sporadic Alzheimer’s disease: correlation with amyloid PET

Abstract: We fractionated frontal cortical grey matter from human Alzheimer's disease and control subjects into four biochemically defined pools that represent four distinct compartments: soluble/cytosolic, peripheral membrane/vesicular cargo, integral lipid/membranous pools and aggregated/insoluble debris. Most of the readily extractable amyloid-β remains associated with a lipid/membranous compartment. There is an exchange of amyloid-β between the biochemical pools that was lost for the amyloid-β42 species in Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 49 publications
7
98
0
Order By: Relevance
“…To pursue the characterization of octameric species, we attempted to enrich our sample in this oligomer form. To this end, we maintained the concentration of DPC micelles constant and increased the concentration of Aβ(1-42) to mimic the consequences of an increase in the latter in the membrane (12 3D). This analysis resulted in a major peak eluting 1.4 mL earlier than β PFOs LOW_Aβ(1-42), as well as a small peak eluting at the same volume as the major peak detected for β PFOs LOW_Aβ(1-42).…”
Section: Preparation Of a β Pfos Aβ(1-42) Sample Enriched In Aβ(1-42)mentioning
confidence: 99%
See 1 more Smart Citation
“…To pursue the characterization of octameric species, we attempted to enrich our sample in this oligomer form. To this end, we maintained the concentration of DPC micelles constant and increased the concentration of Aβ(1-42) to mimic the consequences of an increase in the latter in the membrane (12 3D). This analysis resulted in a major peak eluting 1.4 mL earlier than β PFOs LOW_Aβ(1-42), as well as a small peak eluting at the same volume as the major peak detected for β PFOs LOW_Aβ(1-42).…”
Section: Preparation Of a β Pfos Aβ(1-42) Sample Enriched In Aβ(1-42)mentioning
confidence: 99%
“…However, by focusing exclusively on Aβ aggregation in solution, the membrane is overlooked. Indeed, a large number of studies have shown that the interaction of Aβ with the membrane results in the formation of membrane-associated oligomers, whose formation is considered to be directly responsible for compromising neuronal membrane integrity (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This difference needs to be taken into account when interpreting our findings on connectivity effects associated with β-amyloid vs. tau. However, β-amyloid effects may manifest in the long term, considering that aggregation of β-amyloid has been estimated to take about 19 years from β-amyloid positivity-threshold to mean values observed in AD dementia (Roberts et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The initial investigation into the ability of NB‐360 to suppress the formation of Aβ plaques was done in the rather “mild” APP51/16 mouse model (Neumann et al, ). APP51/16 mice are one of the “slowest” mouse models for Aβ accumulation with a deposition rate of approximately 1.7 μg Aβ40·g −1 brain tissue·month −1 , but compared with the rate of Aβ deposition in the human AD brain (0.02 μg·g −1 tissue·month −1 ; Roberts et al, ), the rate of Aβ deposition in APP51/16 mice is around 100‐fold faster. Plaque deposition in APP51/16 mice starts at around 12 months, and the phase of plaque growth lasts until the mice are very old (>20 months; Rijal Upadhaya et al, ).…”
Section: Effects Of Nb‐360 Treatment On Aβ Pathologymentioning
confidence: 99%